Koordinasi Pada Bagian Protokol dan Komunikasi Pimpinan Dalam Meningkatkan Pelayanan di Lingkungan Sekretariat Daerah Kabupaten Supiori - Hasim, Djamil; Pangaribuan, Tetty; Rijal, Rijal (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to describe and analyze Coordination in the Protocol and Leadership Communication Section in Improving Services within the Regional Secretariat of Supiori Regency. The research is descriptive qualitative in nature. Data analysis techniques through observation, in-depth interviews, documentation, literature study including work procedure mechanisms, directing, synchronization and division of tasks. The results of the research found that the work procedure mechanism carried out in the service was not optimal because the communication carried out had not been accommodated well, but the direction carried out looked good but not optimal. This was because the coordination function between leaders and subordinates in communication was not good and the implementation of activities had not gone well. , the synchronization aspect was found to be not optimal because there was still work being done that was not in accordance with the directions, the division of tasks looked good but was not optimal because there were still vacancies in certain positions. So from the results of this research it was found that coordination in the Protocol and Leadership Communication Section in Improving Services in the Regional Secretariat of Supiori Regency is not yet optimal because there are still many factors that influence the delivery of services including poor communication, inadequate facilities and infrastructure and there is no collaboration yet. both between leaders and subordinates.